Analisis Perlakuan Akuntansi Pajak Pertambahan Nilai Pada PT Hasjrat Abadi Cabang Manado - Ma'Arif, Patrick; Wangarry, Andreas Randy; Pangemanan, Shane A.; Tangon, Joseph N. (Cattleya Darmaya Fortuna, 2025)
PT Hasjrat Abadi Manado Branch is a private company in Manado, and operates in the general trading sector. PT Hasjrat Abadi Manado Branch opened a branch in the city of Manado to serve the needs of the community, especially four-wheeled vehicles with the